Analyzing Feshbach resonances: a 6Li-133Cs case study - Pires, Rico; Repp, Marc; Ulmanis, Juris; Kuhnle, Eva; Weidemüller, Matthias (Physical review. A, Atomic, molecular, and optical physics, 2014)
We provide a comprehensive comparison of a coupled channel calculation, the asymptotic bound-state model (ABM), and the multichannel quantum defect theory (MQDT). Quantitative results for 6Li−133Csare presented and compared to previously measured 6Li−133CsFeshbach resonances (FRs) [Repp et al., Phys. Rev. A 87, 010701(R) (2013)]. We demonstrate how the accuracy of the ABM can be stepwise improved by including magnetic dipole-dipole interactions and coupling to a nondominant virtual state. We present a MQDT calculation, where magnetic dipole-dipole and second-order spin-orbit interactions are included. A frame transformation formalism is introduced, which allows the assignment of measured FRs with only three parameters. All three models achieve a total rms error of <1G on the observed FRs. We critically compare the different models in view of the accuracy for the description of FRs and the required input parameters for the calculations.